OriginalMy: Blockchain technology and business defying a 20th-century regulation. Issue 2 (November 2020) - Moraes, Trícia Karla Lacerda; Cernev, Adrian Kemmer
Blockchain is the century's most notable technological innovation that is reshaping all industries. Notwithstanding, the technology needs to achieve maturity and address critical problems to generate real business value. Consequently, blockchain-based new ventures have been dealing with high-technology-associated pressures to enter this modern market. Most of them are still in the platform proliferation stage, struggling to face serious regulation challenges. Alternatively, there are successful cases in which wise strategic choices allowed companies to overcome the challenges and leverage their business successfully – OriginalMy is one of them. It is a Brazilian born blockchain-based venture aiming to decentralise notary and authenticity contributing to reduce excessive bureaucracy and eventually restrain corruption that is relatively common not only in their country but all over the world. This Teaching Case covers how the venture strove against unpredictable and unfavourable situations to fund and develop its blockchain business. It is supplemented by in-depth Teaching Notes where we craft a synthesised theoretical background to support the complex decision-making process through which the Chief Executive Officer defined the company's fate amid such challenges and uncertainties concerning blockchain technology. The case examines the entrepreneurs behind OriginalMy, its growth, the difficulties it has faced, the upright issues surrounding it and its future outlooks. It draws on theory from high-technology market entry and the inherent pressures of this kind of entrepreneurship, sustained by the strategies and alliances that entrepreneurs can enact to address them.